Enhancers are genes that express organizational RNAs - Mattick, John S. (Frontiers in RNA Research, 2023)
A longstanding enigma in molecular biology is the lack of scaling of protein-coding genes with developmental complexity, referred to as the g-value paradox. On the other hand, a feature of the evolution of multicellular organisms is the emergence of genetic loci termed ‘enhancers’, which control the spatiotemporal patterns of gene expression during development. Enhancer action has been widely interpreted in terms of an early model that postulated that transcription factors bound at enhancers are brought into juxtaposition with the promoters of target genes. This model tacitly assumed that there is no trans-acting gene product of enhancers, but subsequent studies have shown that enhancers are transcribed in the cells in which they are active. Like protein-coding genes, enhancers produce short bidirectional transcripts and long alternatively spliced RNAs, albeit at lower levels due to their transitory and cell-specific regulatory functions. The evidence indicates that long noncoding RNAs (lncRNAs) expressed from enhancers (elncRNAs) guide the formation of phase-separated transcriptional hubs and the epigenetic modifications to direct cell fate decisions during animal and plant ontogeny. Many, and likely most, lncRNAs are elncRNAs, which should be recognized as a bona fide class of gene products alongside mRNAs, rRNAs, tRNAs, snoRNAs, miRNAs and others of established function, with sequences specifying elncRNAs comprising an increasing fraction of genomic information as developmental complexity increases.